Rahasia Hukum Islam dalam Ruang Peribadatan - Abidin, Zaenal (Jurnal Adabiyah, 2012)
Islamic law has many aspects. One of them is the philosophy and secrets of Islamic law (hikmah al-syari‘ah or asrar al-ahkam). Not all secrets are known by Moslems, because al-Quran as its primer source does not show its meaning clearly and totally, but it maybe found by observation. Thus, if its secret is not known at present but it will be known later along with human progress which is supported by the development of science and technology, particularly in the field of medicine. The secrets of Islamic law exists in all fikih aspects, especially at space of observance covering taharat (cleanse or purity), salat (prayer), saum (fasting), zakat (donate, alms or charity), and haji (pilgrimage), and the others. Knowledge about the secrets of Islamic law may improve the truth of the teachings of Islam and on the other said, it may add confidence and affirm Moslems’ soul and spirit in doing their obligation.